A comparison study of HRES for electrification of a rural city in Algeria. Issue 3 (June 2023) - Yahiaoui, Adel; Tlemçani, Abdelhalim
Optimization is one of the most important branches of applied mathematics and much research both practical and theoretical has been devoted to it. In this in this paper we have used the software HOMER to solve optimization problem on optimal sizing of three hybrid renewable energy systems involving of PV panel, wind turbine, battery bank, electrolyzer, H2 tank, and fuel cell for possible installation in Timimoun city in Algeria desert. The proposed systems are applied for optimal configuration, minimization of the total net present cost (TNPC ) and cost of energy (COE). The study showed us that each system provides electrical power for this region, TNPC of the PV/Wind/Battery system is 22, 621, 932 $ with COE of 1.673 $/kWh, it is the most expensive system that we cannot adopt because of its high cost. The PV/Wind/Electrolyzer/H2 tank/Fuel cell system is cheaper than the first in terms of TNPC which equal 14, 945, 818 $ with COE of 1.105 $/kWh. This system is also undesirable because it is more expensive than the PV/Wind/Battery/Electrolyzer/H2 tank/Fuel cell hybrid system. The TNPC of this system is 12, 322, 474 $ with COE of 0.912 $/kWh, which makes it cheaper than the first two systems. The results prove that the hybrid PV/Wind/Battery/Electrolyzer/H2 tank/Fuel cell system meet the electrical energy need of the region.